2016
DOI: 10.1038/srep32110
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association between SREBF-1c gene polymorphisms and risk of non-alcoholic fatty liver disease in a Chinese Han population

Abstract: The transcription factor sterol regulatory element-binding protein-1c (SREBP-1c) is a key regulator of lipogenesis and insulin sensitivity, and is associated with non-alcoholic fatty liver disease (NAFLD). Here, we assessed the impact of common single nucleotide polymorphisms (SNPs) in SREBF-1c on NAFLD susceptibility and associated metabolic phenotypes in a Han Chinese population. Four common SNPs (rs62064119, rs2297508, rs11868035 and rs13306741) in the SREBP-1c gene were selected and genotyped in 593 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…In addition, we found that the G allele of the SREBF-1c 3’UTR A30225G (rs11868035) was associated with lower triglyceride levels. In the same way, Peng et al reported that the G allele of the SREBF-1c 3’UTR A30225G (rs11868035) was associated with lower triglyceride levels in non-alcoholic fatty liver disease [19]. Additionally, using bioinformatics tools we determined the potential effect of the SREBF2 and SREBF-1c gene polymorphisms associated with ACS.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…In addition, we found that the G allele of the SREBF-1c 3’UTR A30225G (rs11868035) was associated with lower triglyceride levels. In the same way, Peng et al reported that the G allele of the SREBF-1c 3’UTR A30225G (rs11868035) was associated with lower triglyceride levels in non-alcoholic fatty liver disease [19]. Additionally, using bioinformatics tools we determined the potential effect of the SREBF2 and SREBF-1c gene polymorphisms associated with ACS.…”
Section: Discussionmentioning
confidence: 88%
“…Similarly, in a Danish population, Grarup et al reported in a meta-analysis study that the G allele is associated with a higher risk of T2DM [30]. However, Peng et al studied a Chinese Han population and reported that the 3’UTR A 30225 G and 3’UTR G30009C polymorphisms were not associated with risk of non-alcoholic fatty liver disease (NAFLD) [19]. With regard to the 3’UTR A30225G (rs11868035) polymorphism, we found that the G allele was associated with lower risk of developing ACS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the analysis, patients were grouped in G/G homozygous vs. carriers of the A allele, as in previous literature (33).…”
Section: Methodsmentioning
confidence: 99%